Virtual multi-antenna array for estimating the direction of a transmitter : system, bounds, and experimental results - Quitin, Francois (2019)
A method is proposed to estimate the direction of a radio-frequency transmitter with a mobile single-antenna receiver. By considering the received signal at several points along its trajectory, the receiver implicitly creates a virtual multiantenna array, which can be used to estimate the direction of the transmitter. Virtual arrays differ from conventional multiantenna arrays in two ways: 1) the position and orientation of each antenna in the virtual array depend on the movement of the receiver and are not known a priori; and 2) the local oscillator (LO) frequency offset between the transmitter and the receiver adds a phase offset to the signal received by each antenna of the virtual array, which must be estimated and compensated. The first problem is solved by using an inertial measurement unit, which can provide the relative position of the receiver for short time durations. The second problem is solved by estimating the LO frequency offset jointly with the direction of the transmitter by extending the MUSIC algorithm for multidimensional estimation. We investigate the Cramér-Rao lower bound of the proposed estimator, which provides some insights in the design of our system. We implement our system on a software-defined radio testbed and present some measurement results obtained in a controlled environment.